Imaging phosphor thermometry from T = 20 °C to 450 °C using the time-domain intensity ratio technique. (1st March 2019) - Sutton, G; Greenen, A; Roebuck, B; Machin, G
Abstract: We present an imaging phosphor thermometry system using the time-domain intensity ratio technique and demonstrate surface temperature measurements that are traceable to ITS-90 with a calibration Standard uncertainty of 0.5 °C, over the range 20 °C to 450 °C. The thermographic phosphor used was Mg4 FGeO6 :Mn. Typically, imaging phosphor thermometry systems make use of the intensity ratio of the phosphor emission in two discrete wavelength bands, measured simultaneously using two cameras viewing the same surface. However, difficulties can arise with image registration (the requirement to spatially align the two images) due to lens distortion, non-normal viewing angles and camera alignment, and this can result in large temperature errors. The time-domain intensity ratio technique presented here avoids these difficulties by capturing two images at different times during the phosphorescence decay process using a single monochrome camera. Each pixel of the camera integrates the light collected over the exposure time. By careful selection of an appropriate exposure time, along with the timing of each exposure (image gating), it is possible to collect two specific time integrated portions of the phosphor decay curve. The phosphor decay time can then be calculated quickly and uniquely from the ratio of these two signals and related to the temperature through calibration. With this technique, there is no requirement for high frame-rates and satisfactory results can be obtained using a relatively inexpensive camera provided that suitable triggering and exposure control are available. Here, we provide a description of the technique, the instrumentation, calibration, and preliminary measurement made on a resistively heated steel coupon, where the standard uncertainty for a single imaged pixel (80 μm × 80 μm) was 7.7 °C, 6.6 °C and 3.8 °C at temperatures of 200 °C, 300 °C and 400 °C respectively. Additionally, a sensitivity analysis and an uncertainty budget are provided.